EFEKTIFITAS PELAKSANAAN.ISBAT NIKAH (TERPADU) PADA. SIDANG KELILING DI PENGADILAN AGAMA SUWAWA - OINTU, FEBIOLA A.; KASIM, NUR M.; KAMBA, SRI NANANG M. (GANEC SWARA, 2024)
This research aims to find out about the effectiveness of implementing the marriage isbat at the Suwawa religious court, as well as what factors hinder the effectiviness of implementing the integrated marriage isbat at the Suwawa religious court. This research uses empirical legal research methods, namely the research method is carried out using empirical evidence such as field data as the main data source as well as infoatian obtained from observatians, documentation and interviews.The results of this research can be seen from the stage of the process of implementing the integrated marriage isbat trial which is carried out by the Suwawa religious court which is not efeective and consistent, because every year the quantity of completion of the targer marriage idbat is not yet significant. However, in implementing the integrated marriage isbat, the are factors that hinder the implementation of the marriage isbat, namely that there are still people eho have not registered because they are hampered by the requirements for implementing the marriage isbat. Apart from that, there are technical problems in the field, such as the location of integrated services which is still far away and there are villages that are difficult to reach.